Which are the most valued HIV pre-exposure prophylaxis attributes? A discrete choice experiment among sexual and gender minorities in Peru - Oliver A. Elorreaga; Jazmin Qquellon; Kelika A. Konda; Karen E. Campos; Gino M. Calvo; Thiago S. Torres; Carlos F. Caceres (PLoS ONE, 2026)
Background There is potential demand for pre-exposure prophylaxis (PrEP) in Peru; however, little is known about preferences towards PrEP modalities or the importance of PrEP attributes. Our research focused on which attributes most influence PrEP modalities choice among sexual and gender minorities (SGM). We also assessed how participants’ preferences vary by recruitment strategy and population. Methods We conducted a discrete choice experiment (DCE) in three mutually exclusive groups: (1) Implementation PrEP Project (ImPrEP) participants; (2) Sexually transmitted infections (STI) clinic attendees; and (3) Online respondents via social media outreach. PrEP attributes assessed were presentation, frequency of use, healthcare provider, HIV testing frequency, side effects, and efficacy. For the DCE, each participant was presented with 12 pairs of options with mixed attribute levels and had to choose one option per pair. The data were analyzed using choice-based conjoint analysis, employing Hierarchical Bayes estimation techniques to derive individual-level utility scores. Results From June to October 2021, we recruited 2832 participants, with median age of 27 years (IQR = 22–33); 56.2% completed tertiary education; and 47.1% earned US$232 or less. In general, efficacy (27.5%, 95% CI 26.9–28.1), and frequency of use (21.3%, 95%CI 20.8–21.7) were the most important attributes, with the online respondents the highest importance on efficacy (31.9%, 95%CI 31.0–32.8). Concerned about potential side effects were more common among STI clinic attendees (17.5% [95%CI: 16.9–18.2]) and online respondents (18.8% [95%CI: 18.3–19.3]), while the ImPrEP participants placed the greatest importance on the frequency of use [26.7%, 95%CI 25.6–27.7]. Conclusions Overall, attributes such as efficacy and frequency of use were the most important PrEP attributes across the recruitment strategies; however, current ImPrEP participants placed more weight on frequency than the other groups. Our data may be helpful for future PrEP scale-up strategies, anticipating potential users concerns, and learning from current users.